The theme of poetic call in two poems of Lagar by Gabriela Mistral - Münnich, Susana (Anales de Literatura Chilena, 2022)
<span data-sheets-value="{"1":2,"2":"In this paper, I analyze two poems of Gabriela Mistral (\"La que camina\" and \"La bailarina\" from Lagar) in order to show that her texts are not to be read as an assortment of disparate fragments but rather as a unified set of poems centering around recurring themes. Both \"La que camina\" and \"La bailarina\" share in common the central theme of the poetic call, though each poem follows a different modality. The first one speaks of the fidelity to that call, while the latter speaks of the way in which such a call makes the poet experience the opposites that confront human beings (good and evil, suffering and joy, and the like)."}" data-sheets-userformat="{"2":957,"3":{"1":0},"5":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"6":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"7":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"8":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"10":1,"11":3,"12":0}">In this paper, I analyze two poems of Gabriela Mistral ("La que camina" and "La bailarina" from Lagar) in order to show that her texts are not to be read as an assortment of disparate fragments but rather as a unified set of poems centering around recurring themes. Both "La que camina" and "La bailarina" share in common the central theme of the poetic call, though each poem follows a different modality. The first one speaks of the fidelity to that call, while the latter speaks of the way in which such a call makes the poet experience the opposites that confront human beings (good and evil, suffering and joy, and the like).